Security mechanisms and data access protocols in innovative wireless networks - Pathan, Al-Sakib Khan; Azad, Saiful; Khan, Rasib; Caviglione, Luca (SAGE Publications Ltd, 2018)
Wireless networks play a vital role in shaping today’s network infrastructure. Although in the past, the use of wireless communications was limited to the last-mile connectivity of the network, their convenience and adaptability has led to a variety of innovative wireless technologies that are now arriving at the scene. These include mobile technologies, 4G (LTE, WiMAX), 3G (UMTS, HSPA), Bluetooth, wireless sensor network (WSN), radio frequency identification (RFID), nearfield communication (NFC), mobile ad hoc network (MANET), vehicular ad hoc network (VANET), wireless mesh network (WMN), wireless body area networks (WBAN), and Wi-Fi. An amalgamation of these different technologies will dramatically enhance the usefulness of small-sized Internet-capable devices and potentially would offer a world of truly ubiquitous computing.